COMMUNITY ACQUIRED METHICILLIN SENSITIVE STAPHYLOCCUS AUREUS CEREBRAL ABSCESS IN A PREVIOUSLY HEALTH GENTLEMAN MIMICKING SIGNS OF CAVERNOUS SINUS THROMBOSIS-A UNIQUE PRESENTATION - Aijazi, Ishma; Abdulla, Fadhil M; Ibrahim, Ahmad Elbagir (Journal of Ayub Medical College Abbottabad, 2015)
Central Nervous System (CNS) infections like meningitis and cerebral abscess caused by Staphylococcus aureus are usually seen in patients with neurosurgical interventions or immune compromised patients or patients with cardiac vegetation’s. They are extremely rare in healthy patients. We report a case of a 44 year old Indian gentleman who was perfectly healthy with no known co morbidities, which presented with fever, neck stiffness and altered mental status. He had fulminant staph bacteraemia (as evidenced by persistently positive blood cultures) with meningitis and cerebral abscess. Extensive search was made to find the source of infection, but it was inconclusive. Isolated CNS Methicillin Sensitive Staphylococcus aureus (MSSA) infection in an apparently healthy patient is very rare. This gentleman presented with altered mental status, asymmetrical exophthalmos and multiple cranial nerve palsies. This case highlights the challenge of making early diagnoses of a brain abscess; since it has symptomology mimicking cavernous sinus thrombosis .This is due to the involvement of the cerebellopontine angle and extensive brain oedema and oedema of the retro bulbar tissues. Keywords: Staphylococcus aureus, brain abscess, bacteraemia